Influência da duração da função tardia do enxerto em transplantes renais com doador falecido - Flávia Carvalho Leão Reis (2019)
Introduction: Delayed graft function (DGF), whose more common definition is the necessity of dialysis in the first week after transplantation, is an important prognostic indicator after kidney transplantation. Depending on the severity of the ischemia-reperfusion injury, DGF can have several clinical presentations, with different renal function recovery times. Both the presence and duration of DGF can have an impact on kidney transplantation outcomes. However, this association and its influence on prognosis show conflicting results in the literature. Objectives: Investigate the impact of DGF and its duration on patient and graft survivals, besides the incidence of acute rejection; to study the overall incidence of DGF and risk factors associated with, besides the renal function. Methods: Single center retrospective study including all deceased donors kidney transplants performed between Nov/2008 and Dec/2015 (n=188). Patients were grouped according to graft work standard in immediate graft function (IGF), slow graft function (SGF) and DGF. These patients were divided according to the duration of DGF (< 8 days or ≥ 8 days). Results: The overall incidence of DGF was 62,2%; cold ischemic time ≥ 14,5 hours and donor age ≥ 39 years-old were some of the factors associated with DGF. Higher HLA mismatches was an independent risk factor for prolonged DGF. DGF with duration of more than 8 days was associated with acute rejection and this one was associated with patient death in 3 years. Conclusion: DGF with a duration of more than 8 days, associated with higher HLA mismatches increases the risk of acute rejection but graft loss and patient survival are not affected by DGF, regardless of its duration.